2015
DOI: 10.1016/j.annemergmed.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Sphenopalatine Ganglion Block for Acute Headache in the Emergency Department: A Randomized Placebo-Controlled Trial

Abstract: For patients with acute anterior headache, sphenopalatine ganglion block with the Tx360 device with bupivacaine did not result in a significant increase in the proportion of patients achieving a greater than or equal to 50% reduction in headache severity at 15 minutes compared with saline solution applied in the same manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 21 publications
0
38
0
9
Order By: Relevance
“…The procedure is similarly repeated in the other nostril. The swab does not come into direct contact with the ganglion, however the local anesthetic infiltrates around it in that position [11]. The connective tissue and mucous membrane covering facilitates the spread and penetration of the drug.…”
Section: Main Bodymentioning
confidence: 99%
“…The procedure is similarly repeated in the other nostril. The swab does not come into direct contact with the ganglion, however the local anesthetic infiltrates around it in that position [11]. The connective tissue and mucous membrane covering facilitates the spread and penetration of the drug.…”
Section: Main Bodymentioning
confidence: 99%
“…The second study utilizing Tx360 ® was a randomized, double‐blind, placebo‐controlled trial that evaluated SPG blockade via Tx360 ® with 0.3 mL of 0.5% bupivacaine bilaterally vs. 0.3 mL of normal saline bilaterally for acute treatment in the emergency department of anterior or global‐based headache . Classification of headache type was not performed, and 93 patients were enrolled, with 87 patients completing the study.…”
Section: Pathophysiologymentioning
confidence: 99%
“…In contrast to the SphenoCath ® and Allevio ® catheters, SPG blockade with the Tx360 ® device is administered with the patient seated and upright . Blood pressure and heart rate are recorded pre and postprocedure.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Schaffer et al 16 treated patients with migraines with intranasal SPG block in the ED. Although the study showed no significant reduction in pain when compared to placebo, there was persistent pain reduction 24 hours following treatment.…”
Section: Discussionmentioning
confidence: 99%